2018
DOI: 10.1080/03007995.2018.1501351
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilization in patients with metastatic melanoma receiving first-line therapy with dabrafenib + trametinib versus nivolumab or pembrolizumab monotherapy

Abstract: HRU during 1 L therapy was generally similar between patients initiated on D + T and N/P. Nonetheless, patients initiated on N/P had more outpatient visits, including more outpatient visits for reasons unrelated to drug administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Since cancer staging information is not available in administrative claims, we used an operational algorithm similarly used in previous observational studies to identify patients with metastatic melanoma. 8,[14][15][16][17][18][19] Figure 1 illustrates a graphical representation of the algorithm and the implemented study methods, adapted from the Repeat Initiative's recommendations on study design visualizations. 20 We defined a case of metastatic melanoma as an initiator of one of the commonly used first-line therapies available over the course of the study period.…”
Section: Data Source and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since cancer staging information is not available in administrative claims, we used an operational algorithm similarly used in previous observational studies to identify patients with metastatic melanoma. 8,[14][15][16][17][18][19] Figure 1 illustrates a graphical representation of the algorithm and the implemented study methods, adapted from the Repeat Initiative's recommendations on study design visualizations. 20 We defined a case of metastatic melanoma as an initiator of one of the commonly used first-line therapies available over the course of the study period.…”
Section: Data Source and Study Populationmentioning
confidence: 99%
“…Patients were required to have at least one inpatient or two outpatient diagnoses of malignant melanoma using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) and ICD-10-CM codes during the 6 months prior to the index date (baseline period) on separate days within 30 days, and at least one inpatient or outpatient medical encounter with a diagnosis of a secondary malignant neoplasm in primary position , 30 days before, or 60 days after a melanoma diagnosis. 8,[14][15][16][17][18][19] Patients were also required to have at least 6 months continuous insurance eligibility before and at least 1 month continuous eligibility after the index date to ensure a minimum duration of analyzable information on health care resource use. Patients were excluded if they had other primary malignant tumors during baseline (Data Supplement), were covered by a capitated health plan or one without prescription benefits at index date, and had missing demographic or health plan information.…”
Section: Data Source and Study Populationmentioning
confidence: 99%
“…2 Experience with ipilimumab monotherapy has been reported, although this has been limited to commercially insured populations and/or not limited to the first-line therapy setting. 16,17 A recent analysis by Ghate et al (2018), also conducted among commercially insured patients, assessed HCRU and found no difference in inpatient hospitalizations and emergency department (ED) visits between patients treated with first-line dabrafenib plus trametinib and patients treated with first-line nivolumab or pembrolizumab monotherapy (2.3 vs. 2.2 inpatient hospitalizations per patient-year, respectively; 1.6 vs. 2.1 ED visits per patient-year, respectively). 18 While others have modeled U.S. costs among patients with metastatic melanoma treated with immunotherapies, few data exist on a limited set of immunotherapies.…”
Section: What This Study Addsmentioning
confidence: 99%
“…16,17 A recent analysis by Ghate et al (2018), also conducted among commercially insured patients, assessed HCRU and found no difference in inpatient hospitalizations and emergency department (ED) visits between patients treated with first-line dabrafenib plus trametinib and patients treated with first-line nivolumab or pembrolizumab monotherapy (2.3 vs. 2.2 inpatient hospitalizations per patient-year, respectively; 1.6 vs. 2.1 ED visits per patient-year, respectively). 18 While others have modeled U.S. costs among patients with metastatic melanoma treated with immunotherapies, few data exist on a limited set of immunotherapies. [18][19][20][21] Very little information is available on metastatic melanoma patients treated with all currently available immunotherapies and targeted therapies.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation